Green Procurement and Performance of Food and Beverage Manufacturing Firms in Kenya - Thiga , Henry; Chege, Dennis; Arani, Wycliffe (International Journal of Supply Chain Management, 2023)
Purpose: The purpose of this study was to determine the relationship between green procurement and the performance of food and beverage manufacturing firms in Kenya. Methodology: An explanatory research design was employed in the study. All 172 of Kenya's registered food and manufacturing businesses were considered using the census approach. Using questionnaires, primary data was gathered. This study employed 172 questionnaires. Version 25 of the SPSS statistical program was used to analyze the data. The primary data was analyzed using descriptive and inferential statistical analysis techniques. Descriptive statistics gives the profile of the respondents, that is, the frequencies and their percentages; whereas inferential statistics adopts a hierarchical, moderated, multiple regression analysis model in order to determine the effect of the explanatory variable. Findings: The study found that there is a correlation of 0.701 between green procurement and the success of Kenyan food and beverage manufacturing companies. Green procurement accounted for 48.7% of the variation in the performance of food and beverage manufacturing firms in Kenya. Unique Contribution to Theory, Practice and Policy: Strategic Choice theory was adopted and validated. By incorporating stakeholders, assessing policy choices, making educated judgments, aligning with capacities, adjusting to changes, minimizing risks, and encouraging cooperation for sustainable procurement practises, Strategic Choice Theory could assist Kenya in developing a complete green procurement policy. The study found that implementing green procurement would; conserve the environment, reduce unnecessary costs to a firm, improve customer satisfaction, improve firm reputation, increase product acceptance, and increase the sales volume.